REGULATING FIRMSâ€™ BEHAVIOR IN THE MARKET UNDER THE COMPETITION LAW: ISSUES AND CHALLENGES - Abdul Rahman, Nasarudin; Ahamat, Haniff; Khan, Mushera Ambaras (Jurnal Media Hukum, 2013)
The objective of competition law is to protect the process of rivalry between firms in the market.Â  It prohibits any anti-competitive behaviors such as cartel and abuse of dominant position. However, in practice regulating firmsâ€™ behaviors in the market is not an easy task.Â  It requires both legal and economic analysis to determine whether a firm is occupying a dominant position and whether the conduct is abusive. This paper seeks to identify the important provisions of â€œanti-competitive agreementsâ€ and â€œabuse of dominant positionâ€ under the Malaysian Competition Act 2010. It is observed that competition law across the counties have been heavily influenced by the UK and EU competition law. Despite the similar concepts applied across the jurisdictions, in practice the implementation differs. This paper seeks to explore the benefits of adopting foreign concepts on competition law and how the rules will be implemented especially in response to the different political, economic and social environment. This paper will also include the approach taken by Indonesia with regard to implementation of foreign ideas on competition law to suit the local need.